Using Collaborative Analysis of Student Learning for Program Improvement and Evaluation - Susan Colby; Monica Lambert (Academic Chairpersons Conference Proceedings, 2015)
Chairpersons will learn the process of Collaborative Analysis of Student Learning (CASL), how to effectively facilitate faculty engaged in this process, and the role of CASL in course and program improvement and evaluation. Participants will examine guiding questions for CASL groups and identify beneficail strategies for facilitating CASL.
Keywords: assessment; program evaluation; student learning outcomes; accreditation; performance-based assessment